2019
DOI: 10.1210/jc.2018-01931
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin Receptor Expression Is Associated With Metastasis and Patient Outcome in Pulmonary Carcinoid Tumors

Abstract: Advance Articles are PDF versions of manuscripts that have been peer reviewed and accepted but not yet copyedited. The manuscripts are published online as soon as possible after acceptance and before the copyedited, typeset articles are published. They are posted "as is" (i.e., as submitted by the authors at the modification stage), and do not reflect editorial changes. No corrections/changes to the PDF manuscripts are accepted. Accordingly, there likely will be differences between the Advance Article manuscri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 40 publications
(47 reference statements)
1
19
0
1
Order By: Relevance
“…For instance, ASNS, one risk biomarker in our study, was reported to function as a therapeutic target in castration-resistant prostate cancer [27]. SSTR1 was widely related to the progression of various cancers [28][29][30], and also functions as a prognostic marker in prostate cancer [31,32]. TRIM14 has been reported to promote invasion in glioblastoma [33] and colorectal cancer [34].…”
Section: Discussionmentioning
confidence: 57%
“…For instance, ASNS, one risk biomarker in our study, was reported to function as a therapeutic target in castration-resistant prostate cancer [27]. SSTR1 was widely related to the progression of various cancers [28][29][30], and also functions as a prognostic marker in prostate cancer [31,32]. TRIM14 has been reported to promote invasion in glioblastoma [33] and colorectal cancer [34].…”
Section: Discussionmentioning
confidence: 57%
“… 35 The expression of somatostatin receptors has also been found to be associated with prognosis in patients with pulmonary carcinoids. 36 Further studies taking Ki-67% and somatostatin receptors into account will need to be undertaken to construct more predictive nomograms. In addition, further research could also be conducted to determine whether our nomogram can be applicable to other patient cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 summarizes information on the antibodies used as well as the staining details. These antibodies have previously been used by our research group also including negative controls (23), and their specificity have been confirmed by Western blot and in vitro receptor autoradiography (24, 25, 26, 27, 28). Antibody binding was visualized using the polymer-based OptiView and UltraView Universal DAB Detection Kit (Ventana Medical System, Inc., Tucson, AZ, USA) or the EnVision Detection Systems (Dako, Agilent Pathology Solutions).…”
Section: Methodsmentioning
confidence: 92%
“…The antibodies used in our study have been previously used and verified (25, 26, 27, 28, 33) with Western blotting and/or in vitro somatostatin receptor autoradiography. The same antibodies have previously been used by our research group for a study on pulmonary carcinoid tumors (23) as well as pheochromocytomas and paragangliomas (antibodies for SST 2 -SST 4 (34)). We stained control tissue (pancreas and small intestine) to serve as a test for the functionality of the staining protocol as well as internal negative control.…”
Section: Discussionmentioning
confidence: 99%